Phytomass mapping of the "seridó caatinga" vegetation by the plant area and the normalized difference vegetation indeces - Costa, Thomaz Corrêa e Castro da; Accioly, Luciano José de Oliveira; Oliveira, Maria Ap. José de; Burgos, Nivaldo; Silva, Flávio Hugo Barreto Batista da (Scientia agricola, 2002)
Phytomass is a critical information for economic and environmental activities like the establishment of policies for timber resources, forest management, studies of plant nutrient cycling, CO2 sink, among other. The phytomass of a Caatinga area was obtained by an empirical method using normalized difference vegetation index (NDVI) of Landsat images, the plant area index (PAI) and the phytomass inventory. At a first stage, linear, logarithmic and non-linear models were developed and tested. Bush and tree specimens were considered in the study, so that most of the individuals that contribute to the spectral answer detected by satellite images were included. At a second stage, the orbital parameter NDVI was used to map the PAI, which was used to map the phytomass, based on the relationship of this phytomass as a function of PAI. The residues between measurements and estimates based on NDVI varied from 0 to 84%, while the residues of total dry weight of phytomass per ha obtained by mapping and by dendrometrical equations varied from 5 to 104%, with a large trend of 166 and 448% in open Caatinga areas, due to the contribution of the herbaceous stratum to NDVI. A fitomassa, principalmente arbórea, é informação necessária em atividades econômicas e ambientais, como políticas de uso do recurso madeireiro, manejo florestal, estudos de ciclagem de nutrientes, absorção de CO2, entre outros. A finalidade deste estudo foi a verificação de um método empírico para o mapeamento da fitomassa da Caatinga do Seridó, integrando-se um inventário de fitomassa, o índice de área de planta (IAP) e o índice de vegetação da diferença normalizada (NDVI), por meio de imagens Landsat TM. Na primeira etapa foram desenvolvidos e testados modelos lineares, logarítmicos e não lineares. A abordagem de tamanho foi arbustiva e arbórea, incluindo-se a maior parte dos indivíduos que contribuem na resposta espectral mensurada por imagens de satélite. Em uma segunda etapa utilizamos o parâmetro orbital, NDVI, para o mapeamento do IAP, que por sua vez, foi utilizado para mapear a fitomassa. Os desvios entre mensurações de IAP e estimativas a partir do NDVI, variaram de 0 a 84%, enquanto que os desvios entre Peso Seco Total de Fitomassa por ha obtidos pelo mapeamento e por equações dendrométricas, variaram de 5 a 104%, com grandes tendências de 166 e 448% para áreas de caatinga aberta, provocada pela contribuição do estrato herbáceo no NDVI.